Analisis Sosial Ekonomi Masyarakat Dusun Batu Alang Kecamatan Moyo Hulu Kabupaten Sumbawa NTB Tahun 2023 - Anirawati Anirawati (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This research delves into the socio-economic conditions of Batu Alang Hamlet in Moyo Hulu District, Sumbawa Regency, NTB in 2023. A quantitative method with a descriptive analysis approach was utilized, involving 100 respondents through questionnaires, observation, and documentation. The results of this research the majority of the population exhibits a high level of educational awareness, with most having at least a bachelor's degree, and some are still in the learning process. The productivity of the community is evident in their ability to meet daily needs with an average of two children. About 85% have BPJS insurance, while only 6% have the KIS insurance. Infrastructure and the environment, including access to clean water, sanitation, wells, and toilets, are considered adequate. Waste management is still basic without recycling facilities. Security is relatively good, with only 7% witnessing conflicts, while theft (67%) and narcotics-related crimes (25%) are common. The entire population adheres to Islam, with a 95% belief in religious figures. The economy of Batu Alang Hamlet is supported by various occupations such as farmers, traders, and blacksmiths. Average income ranges from < 1 million to 30 million, while expenditure levels, both for food and non-food items, range from < 1 million to 5 million. The economic infrastructure is considered quite adequate by 90%, but entrepreneurial interest remains low, with 35% expressing no interest.